Polityka informacyjna miasta Katowice w obszarze polityki (pro)rodzinnej na przykładzie programu pn. ,,Nas Troje i więcej” - Zasępa, Bożena (Political Preferences, 2017)
The information policy of the City Katowice in the area pro-family policy on the example of the program „Nas Troje i więcej” (“The Three of Us and More”) The presented article concerns the information policy conducted by the local authorities of the City of Katowice during the implementation and execution of the program for families called „Nas Troje i więcej” (“The Three of Us and More”). The program has been approached in terms of case study in the field of internal communication in the commune understood as a process of exchanging information and dialog of the commune entities (stakeholders). The study covered the years 2011–2016, and their objective was to analyze selected tools of social communication in terms of function of medium, its content, type of communication (one or two-sided) and the capacity of communication channels. The study took into account both obligatory and optional instruments. Key words: social communication, information policy, local family policy